Socio-cultural experiences of Nigerian immigrant families: maintenance of 'family togetherness' in Norway - Wickliffe, AnjolaOluwa TemilolaJesu (2018)
Family, being considered the basic unit of the society, is vital in every human being’s life. Be it a family in contemporary terms or according to the ideal, traditional meaning, there is a need for all members of that family to be united which in return births a good society. However, one family’s experience cannot be used to determine another family’s experience, but some similarities can occur from which we may learn valuable ways among these families. Is with this knowledge and the dichotomous experiences of some Nigerian immigrants in Norway (in Stavanger particularly, where this research was conducted) that this research dwelled on. The dichotomous experiences were that some Nigerians felt they could live in Norway comfortably with their beliefs and values while some others did not feel comfortable. I therefore aimed towards discovering their experiences in keeping their families together by their cultural norms while imbibing Norwegian norms as well as the management strategies used in negotiating through the Norwegian society. In order to achieve this, two research questions were my guide: "how do Nigerian families experience socio-cultural domains while living in Norway? and what are their management strategies in negotiating through the Norwegian society and staying together?" Through qualitative research method and one interpretive framework (social constructionism), semi-structured, face to face, in-depth interviews were conducted at participants’ choice of location such as their homes (four participants) and public spaces (two participants). Narrative analysis was my analytical tool in coding and analysing my data from participants, till concise findings were achieved. Relevant experiences of Nigerian families were provided by six Nigerian adults who are in a heterogenous relationship, and have children. These adults have lived with their families in Norway for at least five years. They were recruited through purposive snowballing method and personal, first time requests. Findings showed some similarities among all participants which are the practice of the Christian faith which helped them in their interaction within their families. They felt the need to build social bridges, deliberately, by learning the Norwegian language to be able to integrate into the society and communicate with their children. They sustained some of their African culture in the way they dressed at times, the house chores done. There was the reality of transnational relations of living in Norway but having the possibility to return to Nigeria temporarily or permanently, thus the need to be knowledgeable of the Nigerian culture. On the average, they felt Norway was a good place to live in. Some differences were also discovered in terms of how they negotiated with their children, the kind of activities done together and the manner they were done. Conclusively, the dichotomous experiences of some Nigerian immigrants that led me to undertake this research was replicated to some extent in my research findings. This therefore implies that certain things need to be addressed in the society in a collaborative fashion, between immigrants and Norwegian authorities representing the Norwegian system.6 Findings were not based solely on my opinion but passed through rigour to ascertain its credibility, transferability, dependability and confirmability. Research participants and my supervisor served as checks on the conclusive results.